Antifungal activity of plant essential oils and selected Pseudomonas strains against Phomopsis theicola - Starović, Mira; Ristić, Danijela; Aleksić, Goran; Pavlović, Snežana; Özcan, Mehmet Musa; Knežević, Magdalena; Jošić, Dragana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
Development of natural plant protection products as an alternative to synthetic fungicides is of significant importance regarding the environment. This study was carried out with an objective to investigate in vitro antifungal activities of several essential oils extracted from oregano, basil, myrtle and Turkish pickling herb, and the plant growth-promoting rhizobacteria in the genus Pseudomonas, against the phytopathogenic fungus Phomopsis theicola. Microdilution methods were used to determine the minimum inhibitory concentrations (MIC) of selected antimicrobial essential oils (EOs). All EOs exhibited significant levels of antifungal activity against the tested fungal isolates. The oregano EO was found the most potent one (MIC – 5.5 μg/mL), followed by basil (MIC – 75.0μg/mL), myrtle (MIC – 775 μg/mL) and Turkish pickling herb (MIC - 7750 μg/mL). Inhibition of Ph. theicola mycelial growth was observed for all tested Pseudomonas spp. strains. K113 and L1 strains were highly effective and achieved more than 60% of fungal growth inhibition using the overnight culture and more than 57% inhibition by applying cell-free supernatants of both strains. A future field trial with K113 and L1 cultures and cell-free supernatants, containing extracellular metabolites toward Ph. theicola, will estimate their effectiveness and applicability as an alternative to chemical protection of apple trees.
Keywords: Essential oils; Pseudomonas spp; PGPR; Phomopsis theicola; Antifungal activity